Financial Inclusion and Bank Competition in Sub-Saharan Africa - Mengistu, Azanaw; Perez-Saiz, Hector (Washington, D.C. : International Monetary Fund, 2018)
In this paper we study how competition and financial soundness affect financial inclusion in Sub-Saharan Africa (SSA). We use detailed individual-level survey data, combined with key country-level indicators of bank competition and financial soundness, to study the effect on the adoption of several financial products (bank accounts, credit and debit cards, and bank loans). We find that more competition tends to increase the probability of access to these financial products. On the contrary, we do not find strong evidence of the effect of bank-balance sheet variables (i.e. capital adequacy or liquidity) on borrowing by individuals. Our results may help policy makers design regulations that could improve financial inclusion, which could potentially impact economic growth and long-term economic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet